Effect of stimbiotic on growth performance, nutrient digestibility, oocyst shedding, blood profiles, and intestinal microbiota in necrotic enteritis-challenged broiler - Seyeon Chang; Woogi Kwak; Jihwan Lee; Seonwoong Kim; Dongcheol Song; Jaewoo An; Sehyun Park; Kyeongho Jeon; Hyuck Kim; Jinho Cho (Animal Biotechnology)
This experiment was conducted to investigate the effect of stimbiotic (STB) in broilers with necrotic enteritis (NE). A total of 180 one-day-old Arbor Acres (initial body weight of 34.81 ± 1.04 g) were used in this experiment for 32 days. All broilers were randomly allocated into six treatments, and each experimental group had 10 replicate cages with three broilers per cage. The experiment was conducted in a 2 × 3 factorial design consisting of two levels of challenge (challenge and non-challenge) and three levels of STB (0, 0.05, and 0.1%). The NE challenge significantly decreased (P < 0.05) growth performance, heterophil levels in blood, and intestinal lesion scores compared to the non-challenge group. Supplementation of 0.05% STB significantly decreased (P < 0.05) feed conversion ratio and the number of oocysts per gram of feces compared to the supplementation of 0 and 0.1% STB. At the genus level, the supplementation of 0.05% STB significantly decreased (P < 0.05) the abundance of Enterobacterales compared to the other groups on d 32. In conclusion, supplementation with 0.05% STB in a diet could positively regulate the fecal microflora and alleviate the decline in growth performance and nutrient digestibility caused by NE.